Characterization and source analysis of trace metal pollution in coastal shallow marine sediments, Wanning area, Hainan Island, China - Suimiao Wang; Suimiao Wang; Xianqin Wang; Xianqin Wang; Zhaofan Wang; Zhaofan Wang; Guangfei Guo; Guangfei Guo; Liang Chen; Liang Chen; Zanhui Huang; Zanhui Huang; et al. (Frontiers in Marine Science)
IntroductionCoastal shallow marine sediments serve as important sinks for trace metals and are crucial indicators of anthropogenic pollution. The Wanning area of Hainan Island has experienced rapid coastal development and intensified aquaculture, raising concerns about metal contamination.MethodsIn this study, 57 surface sediment samples were collected from the coastal shallow sea of the Wanning area. The concentrations of seven trace metals (As, Hg, Cu, Zn, Cd, Pb, and Cr) were determined. Pollution levels were evaluated using the Nemero multifactor pollution index, and source apportionment was conducted through the Positive Matrix Factorization (PMF) model.ResultsThe average concentrations of As, Hg, Cu, Zn, Cd, Pb, and Cr were 11.40, 0.037, 11.36, 51.69, 0.10, 24.53, and 45.86 mg/kg, respectively, which generally comply with China’s Class I Marine Sediment Quality Standard. While the overall pollution level was low, localized hotspots of As, Cu, Cr, and Pb were identified. The PMF model identified four major pollution sources: aquaculture-related fish medicine (Factor 1, 17.9%), urban wastewater and farm feed (Factor 2, 30.5%), agricultural pesticide use (Factor 3, 17.3%), and maritime transportation (Factor 4, 34.3%).DiscussionThe results indicate that the primary contributors to trace metal pollution in the Wanning coastal area are human activities, including maritime transport, aquaculture, and agriculture. These findings highlight the need for targeted pollution control measures to ensure sustainable coastal development and marine environmental protection.